Virtual Field Trip Learning Video Based on Subak Local Wisdom for Fourth-Grade Elementary School Students - Ni Komang Vera Nawa Laksmi; Anak Agung Gede Agung; Ni Luh Putu Agetania (Jurnal Edutech Undiksha, 2025)
Effective learning requires innovation in the learning media used, especially to clarify contextual material. However, the limited use of technology in learning media often reduces the effectiveness of student understanding, thus affecting low learning outcomes. This study aims to develop virtual field trip learning video media based on local wisdom of Subak. This type of research is R&D using the ADDIE model procedure. The subjects of this research trial were several experts and fourth grade students. Data collection methods used tests, questionnaires and interviews. Data analysis techniques used quantitative descriptive, qualitative descriptive, and inferential statistics. The results of the study obtained were material expert tests of 91.1% (very good), learning design expert tests of 92.5% (very good), learning media expert tests of 91.6% (very good), individual trial results of 97.22% (very good), small group test results of 94.90% (very good) and the results of the effectiveness test showed an increase in average learning outcomes after using virtual field trip learning videos based on local wisdom of Subak. So it can be concluded that virtual field trip learning videos based on local wisdom of Subak are feasible and effective to be used in natural and social science subjects in elementary schools. The implication of this study is that the use of virtual field trip video media can increase students' learning motivation which then affects the improvement of student learning outcomes.